2012
DOI: 10.1089/bsp.2012.0224
|View full text |Cite
|
Sign up to set email alerts
|

Is H5N1 Really Highly Lethal?

Abstract: Medicine for Policymakers is a Journal column that provides decision makers with brief explanations of the meaning and implications for biosecurity of clinical issues. The articles describe, for a nonmedical audience, hospital practices, medical challenges, healthcare delivery issues, and other topics of current interest. Readers may submit ideas to the column's editor, Amesh A. Adalja, MD, through the Journal's editorial office at jfox@upmc-biosecurity.org .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In addition, a number of seroepidemiologic studies have been conducted over the last 15 years. These studies have recently been reviewed by several groups, including by 2 of the authors of this paper [1,7,8]. Although there was considerable overlap, the studies included in these reviews were not identical; however, all 3 recent reviews and prior reviews [9] have found that most serosurveys reported no specimens showing antibody evidence of H5N1 infection and that of those serosurveys that did have positive findings and followed WHO criteria for serologic testing of patients with prior infection, the rates of positives were <3%.…”
mentioning
confidence: 99%
“…In addition, a number of seroepidemiologic studies have been conducted over the last 15 years. These studies have recently been reviewed by several groups, including by 2 of the authors of this paper [1,7,8]. Although there was considerable overlap, the studies included in these reviews were not identical; however, all 3 recent reviews and prior reviews [9] have found that most serosurveys reported no specimens showing antibody evidence of H5N1 infection and that of those serosurveys that did have positive findings and followed WHO criteria for serologic testing of patients with prior infection, the rates of positives were <3%.…”
mentioning
confidence: 99%